INDIVDIDUAL TAXPAYER OPPORTUNITIES ON TAX COMPLIANCE - Prianto Budi Saptono; Muhammad Akbar Aditama (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2022)
The OECD provides recommendations to improve taxpayer compliance in Indonesia by reducing tax avoidance practices. However, most of the research conducted in Indonesia currently discusses individual taxpayers' economic, psychological or moral factors, intending to encourage taxpayers to comply voluntarily. Meanwhile, Kleven et al. argue that this tax avoidance can occur if the Taxpayer has the opportunity to avoid it. Therefore, the Withholding tax system avoids a tax system that can be used as a solution in closing the opportunity for individual taxpayers to do so. This research uses a quantitative approach with descriptive analysis techniques and linear regression models with the research location being carried out at the Jakarta Matraman Tax Service Office. The analysis results show that third parties as a form of supervision and closing the opportunity for individual taxpayers to avoid tax have a positive and significant effect of 73% on tax compliance. Every Taxpayer has an opportunistic attitude to avoid tax, but if there is supervision from a third party, then the Taxpayer tends to comply with his tax obligations. Thus, tax reporting by third parties can reduce the opportunity for taxpayers to avoid taxes and improve tax compliance